Cross-Generational Understandings of Ageism and Its Perceived Impacts on Personal-Public Health. Issue 7 (3rd October 2022) - Mayo, Diana M.; Meuser, Thomas M.; Robnett, Regula H.; Webster, Megan E.; Woolard, Carly E.
ABSTRACT: In 2016, the World Health Organization (WHO) launched a global campaign to combat ageism, emphasizing its potential harm to personal and public health. This qualitative focus group study explored generational differences in understanding the WHO's definition and impact of ageism among baby boomers (ages 60–72; n = 17) and silent generation members (ages 78–85; n = 10). Verbatim transcripts were analyzed via a grounded theory approach, and representative themes and quotations were extracted by consensus. Members of both age groups initially downplayed personal impacts of ageism in favor of a broader discussion of age-related discrimination on a societal level. As each discussion progressed, however, participants acknowledged economic, social, and health impacts linked with ageism, but primarily for others. Both groups noted ageist actors in places of employment, healthcare settings, restaurants, retirement communities, and within family networks. Interestingly, each group rated risk of harm by ageism as greater for the other group. Our findings highlight challenges associated with the translation of a broad public health campaign to engage specific stakeholder subgroups. We discuss future research, education, and training initiatives across all ages to address the detrimental impacts of ageism.